2018
DOI: 10.21521/mw.5834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the season on physiological and endocrine traits and on HSP70 in Saanen goats under Mediterranean climate conditions

Abstract: This study was conducted to determine the impact of heat stress on some physiological and endocrine traits in Saanen goats raised under Mediterranean climate conditions. The effects of thermal stress on heart rate (HR), respiration rate (RR) and rectal temperature (RT) on plasma total trii-odothyronine (T3), thyroxine (T4), Cortisol (C), and HSP70 concentrations were evaluated on twenty two Saanen goats of different ages in the second week of April 2013, July 2013, October 2013 and January 2014. Climatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Regarding the COR peak observed in SUP ewes at the last sampling, different papers report similar effects by heat stress in small ruminants [ 46 , 47 ]. The serum COR levels were the highest during summer [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and positively correlated with ambient temperature, showing reverse trends and negative correlations with TH [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Moreover, during thermal stress, feed-restricted ewes [ 51 ] and rams [ 25 ] showed less increase in cortisol blood concentrations: therefore, if the nutritional deficit is added to thermal stress, the animals can adjust their response, avoiding the potential adverse effects of extreme cortisol action, as it could be the case of the UNS group of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the COR peak observed in SUP ewes at the last sampling, different papers report similar effects by heat stress in small ruminants [ 46 , 47 ]. The serum COR levels were the highest during summer [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and positively correlated with ambient temperature, showing reverse trends and negative correlations with TH [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Moreover, during thermal stress, feed-restricted ewes [ 51 ] and rams [ 25 ] showed less increase in cortisol blood concentrations: therefore, if the nutritional deficit is added to thermal stress, the animals can adjust their response, avoiding the potential adverse effects of extreme cortisol action, as it could be the case of the UNS group of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The farm where our ewes were kept suffered a lot of damage, as well as the houses of the farmers, so it was not possible to carry on the intended further controls, and the overall situation after the earthquake could have direct and indirect effects influencing the results. Despite this accident, fortunately, we had the possibility to have some indication from research performed on other ewes of the same flock, which showed that the feed supplementation had a positive effect on resistin production in the sheep uterine glands [ 52 ] and in the apelinergic system expression in both mammary glands and female reproductive apparatus [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Рівень трийодтироксину найвищий узимку та навесні, а найнижчий восени, а тироксину -взимку був статистично вищим, ніж в інші сезони (Р < 0,05), особливо восени. Білок теплового шоку 70 (HSP70) у плазмі виявився навесні статистично низьким (Р < 0,05), його зміни відображали коливання значень ТВІ в різні сезони, особливо за термічного стресу влітку (Yilmaz et al, 2018).…”
Section: вступunclassified
“…Зааненські кози можуть адаптуватися до сезонних змін погоди та екологічних умов регіону. Автори з Туреччини використали розрахунки за формулою ТВІ = T -(0,31 -0,31 • RH) • (T -14,4), яку запропоновано для овець, означають відсутність теплового стресу при значенні ТВІ < 22,3, стрес середньої сили в інтервалі 22,3 ≤ ТВІ < 23,3, загрозливий -23,3 ≤ ТВІ < 25,6, а надзвичайний при перевищенні 25,6 (Yilmaz et al, 2018).…”
Section: обговоренняunclassified